A novel technique for forehead and eyebrow reconstruction using a temporal hairline flap combined with a free forearm flap: a report of two cases. Issue 1 (30th January 2022) - Hihara, Masakatsu; Hikiami, Rina; Mitsui, Toshihito; Kakudo, Natsuko; Okamoto, Maki; Kuro, Atsuyuki; Kusumoto, Kenji
Abstract: We herein report a novel technique for managing large forehead skin defects that include the eyebrows and upper eyelid. Case 1 was of a 55-year-old woman with an eccrine carcinoma (T2N0M0) at the right forehead, resulting in a skin defect 15 cm in diameter. Case 2 was of an 81-year-old man with a malignant peripheral nerve sheath tumor (T1a N0M0) at the left forehead, resulting in a skin defect 18 cm in diameter. A pedicled temporal hairline flap and free forearm flap were combined and placed on the defect, and good eyebrows and forehead morphology was ultimately achieved.